If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A(x + -2)(x + -3) = 0 Reorder the terms: A(-2 + x)(x + -3) = 0 Reorder the terms: A(-2 + x)(-3 + x) = 0 Multiply (-2 + x) * (-3 + x) A(-2(-3 + x) + x(-3 + x)) = 0 A((-3 * -2 + x * -2) + x(-3 + x)) = 0 A((6 + -2x) + x(-3 + x)) = 0 A(6 + -2x + (-3 * x + x * x)) = 0 A(6 + -2x + (-3x + x2)) = 0 Combine like terms: -2x + -3x = -5x A(6 + -5x + x2) = 0 (6 * A + -5x * A + x2 * A) = 0 (6A + -5xA + x2A) = 0 Solving 6A + -5xA + x2A = 0 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'A'. A(6 + -5x + x2) = 0 Factor a trinomial. A((2 + -1x)(3 + -1x)) = 0Subproblem 1
Set the factor 'A' equal to zero and attempt to solve: Simplifying A = 0 Solving A = 0 Move all terms containing A to the left, all other terms to the right. Simplifying A = 0Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing A to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Add 'x' to each side of the equation. -1x + x = -2 + x Combine like terms: -1x + x = 0 0 = -2 + x Simplifying 0 = -2 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 3
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing A to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Add 'x' to each side of the equation. -1x + x = -3 + x Combine like terms: -1x + x = 0 0 = -3 + x Simplifying 0 = -3 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
A = {0}
| 2+m=-10 | | 6x+9=-108-7x | | -8q-3(q+4)=q+7 | | 6x+9=-1008-7x | | x-(-3)=-1 | | -4y-13=9y+13 | | -3+9x=3(x+6) | | 18b=-234 | | 2x+30=12x | | 3c+c=48 | | 4q+2(-8+3q)=3 | | 8x-73=3x-13 | | 3x-7=7x-9 | | -11n=99 | | 2-5v-6v=2 | | 2-5v-6v=23 | | 12-7x=144-35x | | 42=-3(4n-2) | | -p-8p=3-6p | | -32=-2v | | -2a+5=5 | | 6(2x-9)=-102 | | -4n=-n-6 | | 7x^2-6= | | -39x+31=225 | | -12=-x-5x | | 8x+3=9+5x | | 6=14+n | | 3(5+3x)=-3(6-2x) | | 3x+14=x+24 | | -3x+1=-5x+17 | | 6=10-x |